Improvement of dynamic range and repeatability in a refractive-index-sensing optical comb by combining saturable-absorber-mirror mode-locking with an intracavity multimode interference fiber sensor. (31st May 2019) - Oe, Ryo; Minamikawa, Takeo; Taue, Shuji; Nakahara, Takuya; Koresawa, Hidenori; Mizuno, Takahiko; Yamagiwa, Masatomo; Mizutani, Yasuhiro; Yamamoto, Hirotsugu; Iwata, Tetsuo; Nakajima, Yoshiaki; Minoshima, Kaoru; et al.
Abstract: A mode-locked fiber comb equipped with a multimode interference fiber sensor functions as a high-precision refractive-index (RI) sensor benefitting from precise RF measurement. However, its dynamic range and repeatability are hampered by the inherent characteristics of nonlinear-polarization-rotation mode-locking oscillation. In this article, we introduce saturable-absorber-mirror mode-locking for RI sensing with a wide dynamic range and high repeatability. While the RI dynamic range was expanded to 41.4 dB due to high robustness against cavity disturbance, the self-starting capability without the need for polarization control improves the RI sensing repeatability to 1.10 × 10 −8 for each mode-locking activation. The improved dynamic range and repeatability will be useful for enhancing the performance of RI sensing.